2015
DOI: 10.1161/circresaha.115.306751
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Activation Essential for Endothelial–Mesenchymal Transition in Vascular Calcification

Abstract: Rationale Endothelial cells have the ability to undergo endothelial-mesenchymal transitions (EndMTs), by which they acquire a mesenchymal phenotype and stem-cell like characteristics. We previously found that EndMTs ocurred in the endothelium deficient in matrix Gla protein (MGP) enabling endothelial cells to contribute cells to vascular calcification. However, the mechanism responsible for initiating EndMTs is not fully understood. Objective To determine the role of specific serine proteases and sex determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 66 publications
4
128
0
Order By: Relevance
“…Aortic and valvular endothelial cells also have been shown to transition to cells that undergo osteochondrogenesis via the endothelial to mesenchymal transition (EMT) [58, 59]. Cells exhibiting an osteochondrogenic phenotype have the potential to generate mineralized matrix, resulting in calcified deposits [60].…”
Section: Possible Mechanisms By Which Hmgb1 Promotes Cardiovascular Cmentioning
confidence: 99%
“…Aortic and valvular endothelial cells also have been shown to transition to cells that undergo osteochondrogenesis via the endothelial to mesenchymal transition (EMT) [58, 59]. Cells exhibiting an osteochondrogenic phenotype have the potential to generate mineralized matrix, resulting in calcified deposits [60].…”
Section: Possible Mechanisms By Which Hmgb1 Promotes Cardiovascular Cmentioning
confidence: 99%
“…An inhibitor of BMP type I receptor kinases also reduces the lesion calcification in Ldlr −/− mice (12). Recently, it was found that excess BMP activity triggers EndMT allowing the endothelium to contribute cells to the calcifying process (10, 13, 14). …”
Section: Introductionmentioning
confidence: 99%
“…EndMT is a process through which ECs transit into mesenchymal stem cells and gain multipotency (15), prior to differentiating into various cell lineages (13). EndMT has been shown in normal development, such as neural crest formation and cardiogenesis (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies using lineage tracing of endothelial cells have revealed that a significant portion of ECM-producing cells in various pathological conditions is of endothelial origin (estimates vary but usually range between 20 and 30%). Specifically, this has been shown in various models of lung fibrosis and pulmonary hypertension [41][42][43][44]; kidney fibrosis after acute or chronic injury [45][46][47]; the heart after acute ischemic injury such as myocardial infarction and chronic fibrosis caused by constant pressure overload [ [57]; diabetic retinopathy [58]; valve thickening [59]; and the generation of fibroblast-like cells that support tumor growth [60]. However, the field is not without controversy, since other studies have refuted the extent of EndMT contribution in fibrosis and pointed to proliferation and activation of resident fibroblasts as the main source of myofibroblasts after acute or chronic injury [61•, 62•].…”
Section: Endothelial-to-mesenchymal Transitionmentioning
confidence: 99%